(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2013)
Several factors have been identified as contributing to the increase in the number of criminal cases in land dealings. These include the inherent weaknesses in the statutory provisions of the National Land Code 1965 (NLC), the practices at the land administration and registry that are not stable?. The electronic dealings registration system is yet to be fully developed in addition to lack of method for detecting land fraud, corruption and theft of information. The increase in cases of fraud has created a feeling of concern for the security of landowners registered title. This article analyses the problems and offers suggestions to overcome such problems. The proposed solutions are based on comparisons with current developments in Australia, New Zealand and Canada. The solutions offered by Islamic law are also considered. Keywords: fraud, corruption, theft of information, land dealings, solutions